(untitled) (Ozone Therapy Global Journal, 2015)
It is very common, in the daily surgery´s Vet to find Otis´s clinic case and chronic dermatitis which are recurren ton account of mycosis and specially when it´s made of a yeast called Malessezia Pachydermatis, which are settled in dogs´and cats´s ears and skin. The conventional therapy bases on antifurgal systemic orally and/or topics originates resistances, due to there are secundary effects, contraindications, toxicity and also an elevated ecomomic cost. An alternative therapy are the ozonized oils. The mycosis ´case have been contrasted and substantiated un differnent scientific´s articles, but there is not enough clinical´s studies about his use against this yeast. The object of the present study was to assess the efficacy therapeutic of the sunflower oil ozonated oil in these cases. It establish two groups of 25 clinic cases. The first group was about otis´s case and the second group was about dermatitis´cas, all of them was confirmes with the yeast´s presence, both were treated oral or/and topically respectively.After 15 therapics´days noted an improvement in the clinical cases up to 84% for the first group and 80% fos the second group.This study shows the efficacy of the therapic of the ozonated sunflower oil in the otis and dermatist in dogs and cast verus Malassezia Pachydermatis...